Development of the DriMe (Drive in Merauke) Application Based on Community Participation to Support Sustainable Business Management and Service Marketing for Courier and Driver Operators - Tini Adiatma; Nurlela Pandiangan; Maichel Santo Wijaya Mita; Dodhy Hyronimus Ama Longgy (Jurnal IPTEK Bagi Masyarakat, 2026)
Informal transport services in Merauke face challenges in business management, service promotion, and digital access. A growing tension has emerged between existing app-based platforms and manual systems operated via WhatsApp, particularly regarding inconsistent fare structures and lack of transparency. This community service program addresses these issues by empowering local couriers and drivers through digital innovation. The objective is to develop and implement the DRIME application to improve operational efficiency, unify fare systems, and strengthen community-based digital literacy. Using a Participation Action Research (PAR) approach, the study involved drivers and couriers from the initial needs assessment through application design, testing, training, and evaluation. The program produced three mobile applications and one admin website. Training reached 48 participants, and participatory evaluation led to feature improvements, such as automated tax deduction and the official launch of the application on the Play Store.